دور الضحايا في جرائم سرقة السيارات: دراسة استكشافية - محمود، عبدالمنعم شحاتة (جامعة نايف العربية للعلوم الأمنية, 2018)
تناولت الدراسة نتائج مقابلة منضبطة منهجياً مع مئتي مصري سرقت سياراتهم بين عامي 2011 و2013م؛ 90% منهم من الذكور، و92% متزوجون، و65% تتراوح أعمارهم بين 30- 50 سنة و54% تعليمهم جامعي فأعلى، كما أن 98% من السرقات وقعت بالقاهرة الكبرى، 89% منها كانت ليلاً، وكانت السرقة باستخدام المفتاح في 54% من الحالات، وقد استعاد 55% منهم سياراتهم المسروقة. وجاء ترتيب أسباب تفشي سرقة السيارات من وجهة نظر الضحايا كما يلي: غياب الأمن 98%، تعاطي المخدرات 75%، البطالة 67%، ويرون أن الحد منها يتطلب تغليظ العقوبة وإنارة الطرق وتسيير دوريات راكبة وخفض معدل البطالة. وتبين أن صورة الجاني لدى الضحايا: شخص جريء، عاطل، جاهل، طماع، متهور، يشعر بالنقص، حقود، غير متدين، كما أن 7% من الضحايا يرون أن لهم دوراً فيها، تمثل في ترك المفتاح داخلها أو قبول دفع فدية أو وجودهم بمناطق نائية، وقد تم تفسير هذه النتائج في ضوء الدراسات السابقة.
The study addressed the results of a methodologically disciplined interview with 200 Egyptians whose vehicles were stolen in the period between 2011 and 2013. 90% of them are males, 92% are married, 65% are between 30 and 50 years of age, 54% are university educated and above. Moreover, 98% of thefts took place in Greater Cairo, 89% happened at night, thefts using key were in 54% of cases, and 55% of them recovered their stolen vehicles. The reasons for the spread of vehicles theft from the victims’ point of view were as follows: lack of security 98%, drug abuse 75%, and unemployment 67%. Vic-tims believe that reducing vehicles theft requires intensification of punishment, lighting roads, mobile patrols, and the reducing unemployment rate. It was found that the perpetrator’s image as seen by victims was as follows: bold, unemployed, ignorant, greedy, reckless, feels inferior, spiteful, and non-religious. In addition, 7% of the victims believe they have a role in thefts; this role is represented in leaving the key inside the car, accepting payment of ransom and their presence in remote areas. These findings have been interpreted in the light of previous studies.
Keywords: جريمة سرقة السيارات -- مكافحة الجريمة -- ضحايا الجريمة